Penerapan Aplikasi Platform Merdeka Mengajar Terhadap Guru SDN 104256 Rugemuk - Kurniawan, Ade; Malinda, Leni; Ramadianti, Astria Ayu (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to examine the effectiveness of the independent teaching platform in helping teachers understand the independent curriculum and identify the challenges they face. Specifically, the research focuses on the constraints and interest of teachers at SDN 104256 Rugemuk in using this platform. This descriptive research method collects and analyzes data to provide a comprehensive overview of the phenomenon. The findings reveal several challenges faced by teachers, including limited understanding, lack of experience with the platform, low interest in completing tasks, and poor time management. Despite these obstacles, efforts by the school principal, such as inviting mentors, forming teacher working groups, providing coaching, and supplying wifi, have positively impacted the implementation of the platform. As a result, the independent teaching platform has successfully fostered innovation, creativity, and professionalism among teachers at SDN 104256 Rugemuk.